IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY BY PT WOYLA ACEH MINERALS IN GEUMPANG DISTRICT ACCORDING TO THE CONCEPT OF MAQASID SYARIAH - Afna, Nurul; Badri Hasan (JURISTA: Jurnal Hukum dan Keadilan, 2025)
This research examines the functions and applications of corporate social responsibility (CSR) by PT Woyla Aceh Minerals in accordance with the principles of maqasid sharia. The implementation of CSR aims to have a positive impact on community development from moral, social, and other aspects through community participation; however, the application of CSR in the Geumpang sub-district has resulted in water pollution, environmental damage, the destruction of forest ecosystems, and agrarian conflicts. This study focuses on how the CSR implementation by PT Woyla Aceh Minerals can reduce the pollution impacts from gold mining exploration in Geumpang Subdistrict, as well as analysing the effectiveness and function of CSR implementation by PT Woyla Aceh Minerals in Geumpang sub-district from moral, social, and job creation aspects. This research employs qualitative research methods with an empirical juridical approach, which is a legal study that focuses on the direct application or implementation of normative legal provisions in cases or legal events occurring in the community. Data collection techniques included interviews with workers, community leaders, and relevant parties from PT Woyla Aceh Minerals. The results show that the CSR programme of PT Woyla Aceh Minerals has not fully met the strategic needs of the community, including increasing mineral resources, promoting sustainable economic development, and ensuring long-term preservation. Therefore, integrating maqasid sharia is proposed to ensure that CSR not only meets material aspects but also contributes to social and environmental welfare comprehensively and fairly. This research recommends that the government and law enforcement agencies do not grant operational permits to companies without oversight by related parties, by imposing strict sanctions and revoking licenses for irresponsible companies.